Molecularly imprinted polymers and metal-organic framework-based nanomaterial sensors for food and beverage analysis and safety–A review - Favour Ezinne Ogulewe; Akeem Adeyemi Oladipo; Mustafa Gazi (Talanta Open)
Global health is significantly threatened by foodborne diseases and contaminants, highlighting the need for rapid, cost-effective detection methods. Molecularly imprinted polymers (MIPs) and metal-organic frameworks (MOFs) offer promising solutions, overcoming limitations of traditional analytical methods. This review examines the integration of MIPs and MOFs in electrochemical and fluorescence sensors for food analysis, detailing sensing mechanisms, performance factors, and electrode coating advancements. A significant portion of this review is dedicated to exploring the application of MIP and MOF-based sensors for the detection of a wide array of contaminants in food matrices, encompassing antibiotics, hormones, pesticides, mycotoxins, heavy metals, pathogenic microorganisms, food additives, and allergens. Despite progress, a comprehensive understanding of MIP/MOF-analyte interactions is crucial and remains a critical knowledge gap. This review critically analyses this gap, highlighting the imperative for further research aimed at elucidating these mechanisms to optimize sensor performance.